Analysis of Financial Performance of Private Banks in Uzbekistan (International Journal of Psychosocial Rehabilitation, 2020)
This paper focuses on the financial performance of private banks in Uzbekistan. The data were obtained from the analysis of the financial statements of the financial sector issued by the Central Bank of the Republic of Uzbekistan. It covers the activities of 6 existing private banks in the Republic of Uzbekistan. To solve the problem, we used the regression analysis and correlation method. While the volume of bank assets, asset management ratio, and operational efficiency are positively correlated with ROA, the volume of bank assets, asset management, and operational efficiency are also positively correlated with interest income.